Comparison of Different Green Extraction Techniques Used for the Extraction of Targeted Flavonoids from Edible Feijoa (Acca sellowiana (O.Berg) Burret) Flowers - Katarzyna Angelika Gil; Stela Jokić; Ana-Marija Cikoš; Marija Banožić; Martina Jakovljević Kovač; Antonella Fais; Carlo Ignazio Giovanni Tuberoso (Plants, 2023)
This study aimed to investigate the effect of four green extraction techniques (ultrasound-assisted extraction, UAE; supercritical fluid extraction, SFE; subcritical water extraction, SWE; and extraction using deep eutectic solvents, DES) on the extraction of targeted flavonoids from edible feijoa flowers. The bioactive components in the obtained extracts were quantified by High-Performance Liquid Chromatography—Photodiode Array Detector (HPLC-PDA). Moreover, total polyphenol content and antioxidant activity by DPPH•, ABTS•+, FRAP, and CUPRAC assays were investigated. UAE generally gave the highest yields for isoquercitrin and quercetin content (18.36–25.33 and 10.86–16.13 µg/g), while DES extraction with choline chloride:lactic acid (1:2) and H2O content of 50% gave the highest yield of chrysanthemin (90.81 µg/g). The highest yield of flavone (12.69 mg/g) was obtained with supercritical CO2 at 300 bar. Finally, UAE gave the highest total polyphenol content (ca. 64 mg GAE/g) and antioxidant activity at 70 °C during 30 min with 40% (0.84 mmol TEAC/g and 2.25 mmol Fe2+/g, for ABTS•+ and CUPRAC, respectively) and 60% ethanol-water solution (0.49 mmol TEAC/g and 2.09 mmol Fe2+/g, for DPPH• and FRAP, respectively). The eco-friendly extraction techniques resulted in selective methods capable of extracting targeted bioactive compounds from edible feijoa flowers.